SZ_GERICHTE BEK 2020 72 vom 28. September 2020 , Sperre und Beschlagnahme (Betrug, Zweckentfremdung Covid-19-Kredit) - SZ Gerichte (2020)
Sperre und Beschlagnahme (Betrug, Zweckentfremdung Covid-19-Kredit) | Zwangsmassnahmen/Beschlagnahme